2016
DOI: 10.1590/1413-70542016403036315
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pm24, Pm35 and Pm37 in thirteen Egyptian bread wheat cultivars using SSR markers

Abstract: Powdery mildew of wheat (Triticum spp.) caused by Blumeria graminis f.sp. tritici (DC) E.O. Speer Em. Marchal is one of the most important bread wheat diseases in Egypt. All the Egyptian common bread wheat cultivars are susceptible to that disease at seedling and adult stages. Breeding of resistant cultivars is the most economical and environmentally safe method to eliminate the disease and reduce crop losses. Combinations of two or more effective resistance genes may lead to better, more durable resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Moreover, most of the Egyptian genotypes were found to be moderately resistant or susceptible. The absence of immune Egyptian wheat genotypes was reported previously in most of the commercial cultivars (Emara et al, 2016;Draz et al, 2019;Elsayed and Elkot, 2020;Draz et al, 2022). The 19 common resistant genotypes in both experiments were found to be moderately resistant to the studied Bgt isolates.…”
Section: Genetic Variation In Pm Seedling Resistance In the Studied S...supporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, most of the Egyptian genotypes were found to be moderately resistant or susceptible. The absence of immune Egyptian wheat genotypes was reported previously in most of the commercial cultivars (Emara et al, 2016;Draz et al, 2019;Elsayed and Elkot, 2020;Draz et al, 2022). The 19 common resistant genotypes in both experiments were found to be moderately resistant to the studied Bgt isolates.…”
Section: Genetic Variation In Pm Seedling Resistance In the Studied S...supporting
confidence: 76%
“…Unlike rust diseases in Egyptian wheat, little concern was drawn into the genetic control of PM resistance under Egyptian conditions. Some previous studies tested the presence of specific PM resistance genes in the Egyptian wheat germplasm without knocking into the new sources of genetic control ( Emara et al., 2016 ; Elsayed and Elkot, 2020 ; Draz et al., 2022 ). In this study, the association mapping of PM resistance was studied for the first time under Egyptian conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…markgrafii chromosome disomic addition lines (Niu et al 2018), Indian advanced wheat breeding material (Basandrai et al 2016;Sood et al 2020). Emara et al (2016) also observed that eight Pm genes i.e., Pm2, Pm6, Pm12, Pm16, Pm24, Pm35, Pm36 and Pm37 were resistant to 42 isolates of PM at seedling stage. Basandrai and Basandrai (2017) reviewed seedling resistant donors identified among Triticum spp.…”
Section: Testing Of Materials At Seedling and Adult Plant Stagesmentioning
confidence: 90%
“…The total DNA of Sr2, wheat cultivars, and their F1 populations were extracted from 200 mg of 10 days seedlings. The extraction method was carried out according to Emara et al (2016).…”
Section: Molecular Study Dna Extractionmentioning
confidence: 99%